Communicating Prosthetic Prescriptions from Dental Students to the Dental Laboratory: Is the Message Getting Through?. Issue 12 (1st December 2014) - Parry, Glenn R.; Evans, Jane L.; Cameron, Andrew
Abstract : The aim of this research was to investigate the quality of written prosthetic prescriptions provided by fourth‐year dental students to a commercially operated dental laboratory and to ascertain the contribution of interprofessional education to improving prescription quality. Based on guidelines established by the Medicines and Healthcare Products Regulatory Agency of the European Union (Medical Device Directive 93/42/EEC), an audit was conducted prior to and after an educational intervention was delivered by a dental technician to a dental student cohort at one Australian dental school. Prior to the intervention, thirty‐nine dental prosthetic prescriptions were collected, analyzed, and audited to determine the clarity of written communication and instructions from dental student to dental technician. Following the intervention, a further forty prosthetic prescriptions were collected from the same cohort of students and were audited. The audit of the initial prescriptions showed that 85 percent (n=33) did not comply with the recommended conventions. After the intervention, the prescriptions that did not meet the guidelines had fallen to 30 percent (n=12) of the total. Improvements in prosthetic prescriptions submitted by these dental students to the commercial dental laboratory suggest there is an advantage to including a prosthetic prescription‐writing module in dental school curricula.